Komodifikasi Budaya dan Transisi Etik dalam Perkembangan Pariwisata: Kasus di Suku Osing, Indonesia - Nurhadi, Iwan; Sumarti, Titik; Hadi Dharmawan, Arya; S Damanhuri, Didin (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2022)
Tourism development in many cases induces various socio-cultural consequences at the local community level. In Banyuwangi, local government commoditizes traditional rites of the Osing community for tourism purposes. Framed by Granovetter’s social embeddedness and Bentham’s utilitarianism, this study investigated the socio-cultural consequences of tourism development and portrayed how it influenced ethics in tourism activities of the Osing community. Following qualitative research with interviews and observation, the results suggested that Osing economic activities reflected cultural commodification. The cultural commodification expanded social networks in the relational and structural embeddedness that were operated by trust among the actors. While relational embeddedness was recognized on the personal relation, structural embeddedness was identified among government institutions, private sectors, Pokdarwis, and Osing community. Although the cultural commodification was identified, the ethical economic activities remained on collective values, or so called as collective utilitarianisms. The cultural commodification derived to widen social networks, yet the communal ethical economy remained the same. The study proposed community members to construct economic activities based on local values that were utilized to strengthen their socio-cultural identity. The study allowed better understanding of sociological consequences as undergirding framework in policy making and business cooperation.